A coleta da erva-mate pela população cabocla do Vale do Rio do Peixe e Oeste de Santa Catarina: apropriação privada da terra e rupturas (décadas de 1900 a 1940) / The harvest of erva mate (ilex paraguariensis) by caboclo population in West and Peixe valley river of Santa Catarina States (Brazil): Breaks with the advancement of private appropriation (decades 1900 to 1940). - Marlon Brandt; Naiara Sampaio Silva (Sociedade & Natureza)
The article aims to analyze the extraction of erva-mate (Ilex paraguariensis) by caboclo populations in the Western forests of Santa Catarina State, the private land appropriation processes and the disarticulation of the extractive practice of the private land appropriation processes, which becomes more intense from the First Republic decades on. In this region, a significant part of caboclo families was settled since the first decades of the nineteenth century, mostly under the ownership regime, next to the pastoral land property located in the areas of natural grassland. The primary source of income was linked to subsistence agriculture and practices related to the exploitation of forest resources, such as the extraction of erva-mate. The disintegration happens when a new social-spatial dynamics becomes present, inducing the private land appropriation, with the subsequent colonization, the fencing of land and the logging.